No evidence of "weekend effect" for complications of medical and surgical care - Camilla Mattiuzzi; Giuseppe Lippi (Emergency Care Journal)
We performed an electronic search in CDC WONDER online database (years 2018-2022) to explore whether the higher risk of dying during the weekends may be related to complications of medical and surgical care. One-way ANOVA and Tukey's HSD multiple comparison test revealed no significant variation in mean number of deaths during the seven days of the week in the US. No significant difference was observed between the mean number of deaths during the weekend and those recorded during the weekdays (675±130 vs. 711±112; p=0.339). The mean ratio of mortality due to complications of medical and surgical care to the total number of deaths was not significantly different on weekends and weekdays (151 vs. 158×100,000 deaths; p=0.255). The results of this analysis suggest that the so-called “weekend effect” may not be apparently attributable to complications of medical and surgical care and may hence be more related to patient-specific factors.